성인 주의력결핍과잉행동장애 증상과 문제성/병적 도박 간의 관련성 - 이원석; 김문두; 정영은 (Singyŏng chŏngsin ŭihak, 2024)
Objectives Recently, the clinical importance of attention deficit hyperactivity disorder (ADHD) and problem/pathological gambling has been increasing. Studies on the relationship between ADHD and problem/pathological gambling are ongoing worldwide but few are conducted. This study examined the relationship between adult ADHD symptoms and problem/pathological gambling. Methods Data from 500 adults aged 20 to 59 who took part in a community survey were analyzed. All participants completed self-report questionnaires in which demographic variables and ADHD symptoms were assessed using the Adult ADHD Self-Report Scale. Problem/pathological gambling was assessed using a Korean version of the Diagnostic Interview Schedule. Results The prevalence of adult ADHD symptoms was 15.2%. The association between ADHD symptoms and problem/pathological gambling was significant (p<0.001). Additionally, subjects with ADHD symptoms showed a more positive attitude toward gambling than subjects without symptoms. Multivariate analysis revealed a significant relationship between ADHD symptoms and problem/pathological gambling (odds ratio, 2.394; 95% confidence interval, 1.104–5.191; p=0.027). Conclusion Problem/pathological gambling is associated with ADHD symptoms. Therefore, clinicians should provide education and intervention on gambling behavior to subjects with ADHD symptoms. KCI Citation Count: 0